Study of single nucleotide polymorphism DNA in populations of sockeye salmon at Kamchatka, northwestern coast of the Okhotsk Sea, and Chukotka - Anastasia M. Khrustaleva; Ekaterina V. Ponomareva; Maria V. Ponomareva; Natalia V. Klovach (Известия ТИНРО, 2017)
Population structure of Asian sockeye salmon is considered by variability of 45 loci of single nucleotide polymorphism DNA (SNP) in 17 samples from its 10 major spawning grounds at Chukotka, Kamchatka, and northwestern coast of the Okhotsk Sea. General pattern of genetic heterogeneity of sockeye salmon is well corresponded with spatial-geographic structure of the species. Five groups of populations are determined by cluster analysis and AMOVA: the so called nuclear populations at Kamchatka, as the population complexes of the Ozernaja River and Kamchatka River, the group of secondary stocks of the lake-river systems at Koryak coast, and two subperipheral populations of Chukotka and the Okhota and Palana Rivers. The groups split to the south and north complexes. Possible mechanisms of such differentiation with close similarity among populations of South-East Kamchatka and strongly separate population of the Palana and Okhota Rivers are discussed taking into account other markers (microsatellite loci, mtDNA). There is supposed that high differentiation of the Palana and Okhota River sockeye is caused by mutual impact of adaptive (local selection) and demographic (gene drift, effective number decrease) processes in this population.